Competitive Strategies and Performance of Beverages Companies in Rwanda: A Case Study of Bralirwa Plc - Migisha, Divine; Akims, Malgit (European Journal of Business and Strategic Management, 2024)
Purpose: The purpose of this study was to assess the effects of competitive strategies on the performance of Beverages companies in Rwanda, specifically in Bralirwa Plc. The study specifically sought to determine the effect of cost leadership strategy, differentiation strategy, focus strategy, and differentiation Focus Strategy on the performance of Bralirwa Plc. Methodology: This research was descriptive research design, and the study population comprise 206 employees of Bralirwa Plc/Kigali office. Using simple random sampling technique, a sample size of 136 respondents was established using Slovin formula. The researcher used primary data in this study. A closed end questionnaire was utilized. Financial statements of Bralirwa Plc during 10 years period (2014-2023) were also analyzed. Correlation analysis was utilized to assess the data and results generalized for the entire population, while multiple regression was used to test hypotheses. To compute and analyze the data in this study, available statistical product for service solution (SPSS 27) was used. Findings: The correlation analysis revealed a strong positive and significant relationship between cost leadership strategy and performance (r=0.989 and sig=.000<0.01), between differentiation strategy and performance (r=0.944 and sig=.000<0.01), between focus strategy and performance (r=0.961 and sig=.000<0.01) and between differentiation focus strategy and performance (r= 0.945 and sig=.000<0.01) level of significance. The regression analysis revealed that cost leadership contribute 97.9% on the performance in Bralirwa Plc that differentiation strategy contributes 89.2% of the performance in Bralirwa Plc, that focus strategy contributes 92.4% of the performance in Bralirwa Plc, and that differentiation focus strategy contributes 89.3% of the performance in Bralirwa Plc. The study concluded that there were significant and positive effects between Competitive strategies and performance of Bralirwa Plc. Unique Contribution to Theory, Practice and Policy: The study recommended Bralirwa to invest in market research, diversifying product portfolios, and implementing targeted marketing strategies to identify emerging trends and consumer preferences, thereby reinforcing Bralirwa's commitment to differentiation and market leadership.